DEVELOPMENT OF INSTRUMENT PHYSICAL ABILITIES MOUNTAINEERS (VALIDITY AND RELIABILITY TEST PHYSICAL FITNESS AND MOTOR FITNESS MOUNTAINEERS) - Kurniawan, AR.; Rohendi, Andang; Ropi, Ucu Abdul; Chamim, Miftachul (Universitas Pendidikan Indonesia, 2023)
Outdoor sports activities require excellent skills in situations of high physical stress, so physical condition plays a vital role in supporting the success of mountaineering. Objectives; This study aims to test the validity and reliability of the physical fitness and motor fitness components as a reference for determining the optimal physical performance of mountain climbers. Methods; The method used is Research and Development, the participants this 7 mountaineers on 18 peaks for 12 days at an altitude of 3000 MDPL in Indonesia. The sampling technique used was total sampling. The analysis used is content validity and construct validity. Data analysis was carried out, namely the first to sixth steps, namely the stage of developing standard indicators for physical abilities components in terms of physical fitness and motor fitness. The seventh to tenth steps are the instrument development stage. The small-scale test was used as a product development trial to test the validity and reliability of the test instrument. A large-scale test to develop norms and standards for assessing mountaineer's physical abilities test instruments. Result; The components of developing the physical abilities test for mountaineers include physical fitness factors, including cardiorespiratory endurance fitness (Balke test), muscular strength and power (jump decathlon test), muscular endurance (wall squat test), flexibility (Static Flexibility Test – Hip and Trunk), body composition (BMI and % fat content). Motor fitness factors include speed (running 35 m speed test), agility (hexagonal obstacle test), coordination (Hand and eye coordination test), balance (standing stroke test), and reaction time (whole-body reaction). Conclusion; the physical abilities component of mountaineers has a substantial correlation value, and the test instrument can be used as an evaluation method to measure mountaineers' physical and motor fitness.